Notebook [28, Fall 1991] - Leier, Mark (James Mark) (Labour / Le Travail, 1991)
Takes note of forthcoming conferences, a call for papers, and international research projects on European social democracy in World War I, the Communist International, and the complete works of Mikhail Bakunin.